2008
DOI: 10.1080/01904160802463270
|View full text |Cite
|
Sign up to set email alerts
|

Optimum Nutrient Level on Growth, Flowering, and Rhizome Production inCurcuma

Abstract: This study investigated the effect of liquid fertilizer treatments on growth, flowering, leaf mineral content, and rhizome production during forcing of Curcuma alismatifolia 'Chiang Mai Pink' and C. thorelii 'Chiang Mai Snow'. Plants were irrigated with 200 mL of 1.3 g L −1 of 15 nitrogen (N) -7 phosphorus (P) -14 potassium (K) water soluble fertilizer at 0, 1.3, 2.7, 4.0, 5.3, or 6.6 g L −1 weekly. Days to flower, flower stem length, and leaf length were recorded, the mineral contents in leaves were analyzed,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…Our results showed, however, that C. productus plants did respond to nitrogen fertilization already during its first year of cultivation, presenting higher means under 4.8 g N plant ¡1 . Also, Lee, Lee, and Suh (2008) found flowering delay for Curcuma thorelli "Chiang Mai Snow" but not for C. alismatifolia "Chiang Mai Pink" under the same nitrogen dose of 6.6 g L ¡1 , which confirms different responses from distinct species. The authors also had fewer inflorescences from both species under that same dose, reaching a higher number when C. alismatifolia plants were submitted to 2.7 g N L ¡1 , and C. thorelli from 1.3 to 4.0 g N L ¡1 , some of the lowest tested doses.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…Our results showed, however, that C. productus plants did respond to nitrogen fertilization already during its first year of cultivation, presenting higher means under 4.8 g N plant ¡1 . Also, Lee, Lee, and Suh (2008) found flowering delay for Curcuma thorelli "Chiang Mai Snow" but not for C. alismatifolia "Chiang Mai Pink" under the same nitrogen dose of 6.6 g L ¡1 , which confirms different responses from distinct species. The authors also had fewer inflorescences from both species under that same dose, reaching a higher number when C. alismatifolia plants were submitted to 2.7 g N L ¡1 , and C. thorelli from 1.3 to 4.0 g N L ¡1 , some of the lowest tested doses.…”
Section: Resultsmentioning
confidence: 81%
“…Furthermore, Natale et al (2006) also achieved nitrogen positive effects on S and Ca contents, while Camargo, Mello, and Carmello (2008) found that further nitrogen fertilization increased its own content in Aster ericoides stems, even when cultivated in highly fertile soil. Also, Smith, Elliott, and Bridgen (1998) and Lee, Lee, and Suh (2008) found an increase in N contents in leaves of Alstroemeria flower stems and Curcuma spp., respectively, with N supply. Figure 3.…”
Section: Resultsmentioning
confidence: 90%